West Nile Virus outbreak in Sardinia, Italy, in 2011 - Spissu, Nicoletta; Panichi, Giovanni; Montisci, Antonio; Fiore, Filippo (The Journal of Infection in Developing Countries, 2013)
West Nile Virus (WNV) is an enveloped, positive-sense RNA virus belonging to the genus Flavivirus, antigenically related to the Japanese encephalitis complex in the family Flaviviridae. The principal vectors are mosquitoes, in particular Culex spp, and virus amplification seems to occur in susceptible birds that are the principal vertebrate reservoir hosts, whereas humans, horses and other vertebrates are considered incidental or dead-end hosts. The first Italian equine outbreak was reported in late summer of 1998 in Tuscany, in the area surrounding the Fucecchio marshes, where 14 clinical cases of WND in housed equines were recorded. In 2011 WNV appeared for the first time in Sardinia, representing the first clinical cases in equines in Italy in 2011. The outbreak occurred both in humans and in equines. The serological survey performed on 253 equines living in the province of Oristano detected a total of 87 IgG-positive subjects. Among them, 46 horses showed neurological signs such as ataxia, paresis, paralysis, hyperesthesia, muscle fasciculations, seizures, or fever. Nine of them died or were euthanized. In forthcoming years, surveillance of wild birds and insects will be used to forecast the extension and spread of WNV. The information gathered will be used to direct or optimise strategies intended to prevent virus transmission.